The boatman and other stories - O'Callaghan, Billy (Harper Perennial, 2020)
The breathtaking short story collection from the Costa-shortlisted Irish writer. In these twelve quietly dazzling, carefully crafted stories, Billy O'Callaghan explores the resilience of the human heart and its ability to keep beating even in the wake of grief, trauma and lost love. Spanning a century and two continents - from the muddy fields of Ireland to a hotel room in Paris, a dingy bar in Segovia to an aeroplane bound for Taipei - The Boatman follows an unforgettable cast of characters. Three gunshots on the Irish border define the course of a young man's life; a writer clings fast to a star-crossed affair with a woman who has never been fully in his reach; a fisherman accustomed to hard labour rolls up his sleeves to dig a grave for his child; a pair of newly-weds embark on their first adventure, living wild on the deserted Beginish Island. Ranging from the elegiac to the brutally confrontational, these densely layered tales reveal the quiet heroism and gentle dignity of ordinary life. O'Callaghan is a master celebrant of the smallness of the human flame against the dark: its strength, and its steady brightness.